KESADARAN EKOLOGIS; PELESTARIAN LINGKUNGAN DALAM AL-QUR’AN - Andi Eki Dwi Wahyuni; Mardan; Muhammad Yusuf (AL-MUTSLA, 2024)
The interaction of humans and the environment is inseparable. Human dependence on natural resources for their survival is threatened as a result of poor management and exploitation actions making environmental damage worse. The purpose of this interpretation research is so that readers better understand the nature of ecological awareness, verses about ecological awareness, and the urgency of ecological awareness. In this study, a qualitative approach is used with the Maudhu'i interpretation method. As for the results of the research conducted, that ecology is a science about the interaction of living things with their living environment. In Arabic the environment means al-bī'ah. Some verses that explain about ecological awareness are QS. Āli 'Imrān/3: 191; QS. al-Anbiyā'/21: 31; QS. al-A'rāf /7: 10; Qs. al-Qaṣaṣ/28:77; Qs. al-Baqarah/2: 60 Then in Qs. al-A'rāf /7: 56-58. The importance of increasing environmental awareness for humans, because we were created as caliphs (leaders on earth) managers who are responsible for the sustainability of life on earth, not only utilizing but also guarding nature as the mandate given by Allah.